Ecology, diversity and seasonal distribution of wild mushrooms in a Nigerian tropical forest reserve - MOBOLAJI ADENIYI; YEMI ODEYEMI; OLU ODEYEMI (Society for Indonesian Biodiversity, 2018)
Adeniyi M, Odeyemi Y, Odeyemi O. 2018. Ecology, diversity and seasonal distribution of wild mushrooms in a Nigerian tropical forest reserve. Biodiversitas 19: 285-295. This study investigated the ecology, diversity and seasonal distribution of wild mushrooms at Environmental Pollution Science and Technology (ENPOST) forest reserve, Ilesa, Southwestern Nigeria. Mushrooms growing in the ligneous and terrestrial habitats of the forest were collected, identified and enumerated between March 2014 and March 2015. Diversity indices including species richness, dominance, and species diversity were evaluated. Correlation (p < 0.05) was determined among climatic data and diversity indices. A total of 151 mushroom species specific to their respective habitats were obtained. The highest monthly species richness (70) was obtained in October 2014. While a higher dominance was observed in the terrestrial habitat during the rainy and dry seasons (0.072 and 0.159 respectively), species diversity was higher in the ligneous and terrestrial habitats during the rainy season (3.912 and 3.304 respectively). Overall, the highest carpophores in ligneous and terrestrial habitats were recorded in Schizophyllum commune (10,737) and Mycena monticola (760) correspondingly. Correlation analysis revealed that average monthly precipitation positively correlated with the relative abundance of mushrooms in the terrestrial habitat (r = 0.716, p = 0.013). This study shows the diversity of mushrooms at ENPOST forest, thereby necessitating strict and sustainable conservation measures especially those with great economic values.